2019
DOI: 10.1093/mnras/stz177
|View full text |Cite
|
Sign up to set email alerts
|

The nature of PISN candidates: clues from nebular spectra

Abstract: A group of super-luminous supernovae (SL-SNe) characterised by broad light curves have been suggested to be Pair Instability SNe (PISNe). Nebular spectra computed using PISN models have failed to reproduce the broad emission lines observed in these SNe, casting doubts on their true nature. Here, models of both PISNe and the explosion following the collapse of the core of a very massive star (100 M ⊙ ) are used to compute nebular spectra, which are compared to the spectrum of the prototypical PISN candidate, SN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…The nebular spectra of SN 2007bi exhibit strong features of Fe-group elements, which we do not observe in SN 2016iet. In SN 2016iet we observe much narrower lines than in SN 2007bi, closer to the velocities of ∼ 2000 − 4000 km s −1 expected from a PISN (Woosley 2017;Mazzali et al 2019). We also plot a PISN model of a 100 M He core from Mazzali et al (2019).…”
Section: Spectral Comparisonssupporting
confidence: 64%
See 1 more Smart Citation
“…The nebular spectra of SN 2007bi exhibit strong features of Fe-group elements, which we do not observe in SN 2016iet. In SN 2016iet we observe much narrower lines than in SN 2007bi, closer to the velocities of ∼ 2000 − 4000 km s −1 expected from a PISN (Woosley 2017;Mazzali et al 2019). We also plot a PISN model of a 100 M He core from Mazzali et al (2019).…”
Section: Spectral Comparisonssupporting
confidence: 64%
“…However, Nicholl et al (2013) suggested that SN 2007bi was powered by a magnetar central engine with an ejecta mass of only 7 M . The spectra, metallicity, and observational features of SN 2007bi has been shown to be inconsistent with a PISN (Jerkstrand et al 2016;Dessart et al 2013;Mazzali et al 2019). To date, there have been no definitive cases of PISN explosions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the early-time spectra of PTF11rka resemble those of the SLSN 2007bi. In recent work, Moriya, Mazzali & Tanaka (2019b) and Mazzali et al (2019) showed that SN 2007bi is consistent with the explosion of a ∼ 40 M CO core of a massive star (of initial mass probably 60-80 M ). The explosion was not particularly energetic, given the large mass (E k ≈ 4 × 10 52 erg, E k /M ej ≈ 1), which makes the light curve broad.…”
Section: Discussionmentioning
confidence: 94%
“…The unusual light curve of PTF11rka (which was almost as luminous as a GRB-SN; see Fig. 2) and its early-time spectra, characterised by rather sharp, narrow, unblended absorption lines, are reminiscent of SN 2007bi, which was thought to be a pair-instability SN candidate (Gal-Yam et al 2009), although this was later challenged (Jerk-strand, Smartt & Heger 2016;Moriya, Mazzali & Tanaka 2019b;Mazzali et al 2019). These features were reproduced by Moriya, Mazzali & Tanaka (2019b) by adopting a sharp cut in the ejecta distribution with velocity, at 13,000 km s −1 .…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation